Description Of Problem-Solving Skills For High School Students On Virus Materials - Marini Marini; Afandi Afandi; Anisyah Yuniarti (Indonesian Journal of Biology Education, 2022)
This study aims to determine the description of students' problem-solving skills and the description of skills on each indicator of IDEAL problem-solving for high school students in class X on virus material. The subjects of this study were students of class X MIA at a private high school as many as 29 students who had studied virus material. The instrument was used as a test description of IDEAL problem-solving skills, totaling 20 questions consisting of 5 IDEAL Problem-Solving indicators from Bransford and Stein. The results showed that the description of students' problem-solving skills had a percentage of 53% in the unskilled category. The details of the research data on problem-solving skills in the moderately skilled category are indicators identifying problems by 68% and setting goals by 75%, unskilled categories, namely indicators exploring possible strategies by 36%, anticipating results and acting by 47%, and indicators seeing and study by 40%. This study revealed that the factors that hindered unskilled problem-solving skills were student interest, low cognitive ability, and lack of habit of solving problem-solving problems. Ask their English teacher about the current situation of the learning process.keywords: Problem-solving skills, IDEAL Problem-Solving, Virus material.